Analysis of Personality, Leadership, and Organizational Culture on Work Discipline of Honorary Employees of the Binjai City Transportation Service - Nabila Nabila; Muhamad Toyib Daulay; Ikhah Malikhah (Journal of Management, Economic, and Accounting, 2026)
This study aimed to examine the effects of personality, leadership, and organizational culture on the work discipline of honorary employees at the Binjai City Transportation Office. The population of this study consisted of 185 employees, and a total of 65 employees were selected as respondents based on the Slovin formula. The sampling technique used was purposive sampling. The research was conducted in 2025. This study employed primary quantitative data collected through questionnaires and processed using SPSS version 24.0. The data analysis technique used was multiple linear regression analysis. The results showed that personality, leadership, and organizational culture partially and simultaneously had positive and significant effects on the work discipline of honorary employees at the Binjai City Transportation Office. The partial test (t-test) indicated that personality had a regression coefficient of 0.277, a t-value of 4.344, and a significance value of 0.000. Leadership had a regression coefficient of 0.327, a t-value of 4.179, and a significance value of 0.000. Organizational culture had a regression coefficient of 0.351, a t-value of 4.365, and a significance value of 0.000. The simultaneous test (F-test) showed an F-value of 316.524 with a significance value of 0.000. The t-table value was 2.000 and the F-table value was 2.755, indicating that t-count was greater than t-table and F-count was greater than F-table, with a significance value less than 0.05. Therefore, Ha was accepted and Ho was rejected, meaning that hypotheses H1, H2, H3, and H4 were proven and accepted as the results were consistent with the proposed hypotheses. The most dominant variable influencing work discipline was organizational culture, with the largest Beta value of 0.373. Approximately 93.7% of work discipline was explained by personality, leadership, and organizational culture, while the remaining percentage was influenced by other factors. Personality, leadership, and organizational culture had a very strong relationship with work discipline, as indicated by an R value of 0.969.